4 - Leadership Philosophy and Interventions to Support Middle-level Units within Large Academic Institutions: Experiences at the Makerere Peace and Conflict Studies Centre - Nkabala, Helen Nambalirwa; Kanakulya, Dickson (Journal of Higher Education in Africa, 2022)
This article discusses practical lessons on how leadership intervention philosophy can be used to design and ensure that an academic unit within a big institution realises its mandate. The interventions took place at the Peace and Conflict Studies Centre (MPCSC) at Makerere University between 2015 and 2019. The undertaking was guided by systemic leadership intervention philosophy and transformational leadership. The methods used in the intervention included: leadership interventions, secondary data analysis, narrative analysis and autoethnography. The article uses a combination of analytical and auto-biographical reporting styles. Major findings include the following: there is a leadership skilling gap between high-level and mid-level managers in large university units; in large academic institutions, mid-level managers must combine traits and process leadership approaches in order realise progress. Key observations: student enrolment drives achieved a slight improvement in numbers (from 14 % in 2015/2016 to 42 % in 2018/2019); a minor improvement in workstations led to a more than 100 per cent increment in usage by staff and students; the Centre noticed a 63 per cent completion rate of specialised skills training by staff; on average, interdisciplinary research teams perform better than single discipline teams, but the former required extra effort to keep together; the interventions led to a 70 per cent increase in community outreach through avenues such as projects, experiential learning sessions, consultancies, etc.